PENGARUH INFLASI TERHADAP IMPOR DAN EKSPOR DI PROVINSI RIAU DAN KEPULAUAN RIAU MENGGUNAKAN GENERALIZED SPATIO TIME SERIES - Rezzy Eko Caraka; Wawan Sugiyarto; Gustriza Erda; Erie Sadewo (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2016)
In order to support the economy in Indonesia, the government takes the role in formulating fiscal policy, monetary or non-monetary. In addition, it is necesarry also deep concern related to inflation. This is because when inflation is high, the price of goods and services export become relatively more expensive and lead to domestic products and services can not compete with goods and services from abroad. Exports will also tend to descrease followed by an increase in imports from other countries are likely to increase . province of riau and Riau island border with malaysia and sinagpore. Geographical location adjoining give effect to the value of exports and imports Indonesia. Based on the analysis by modeling based on generalized spatio time series it was concluded that in order to control the inflation rate can be done by maintaining adequate supply and distibution of essential commodities. Lowering inflation expectations remained at a high level and perform industrial production to the maximum and do the consumption of local product.